“Dadih Delight Yogurt” Functional Drink Based on Local Food Dadih, Bengkuang and Tapai Ketan Hitam to Control Blood Glucose Levels of Patients with Diabetes Mellitus - Yuniritha, Eva; Pusparini; Yohanes W. Saleky; Fitria, Mona (CV. CENDIKIA JENIUS INDONESIA, 2025)
Diabetes mellitus (DM) is a non-communicable disease with an increasing incidence rate globally, including in Indonesia. The prevalence of Diabetes Mellitus in Indonesia increased from 8.5% in 2018 to 11.7% in 2023. The disease is characterized by high blood glucose levels due to impaired insulin production or action, thus requiring proper management to prevent complications. Diet, physical activity and lifestyle management. Eating a regular diet, as well as engaging in regular physical activity is essential to prevent complications. Functional food options such as probiotics are an alternative to secondary prevention. This study aims to develop a functional drink formula “Dadih Delight Yoghurt” from local ingredients such as curd, bengkuang and black glutinous rice tape to control blood glucose levels of patients with DM. This experimental study used a completely randomized design with one factor and five treatment levels (15-35% addition of bengkuang juice and black glutinous rice tape) with two repetitions. The results showed that the product “Dadih Delight Yoghurt” had good acceptability, with panelists assessing the color, aroma, taste, texture and overal of the product including the categories “somewhat like” and “like”. This indicates that this product has potential as an effective alternative treatment for diabetes mellitus.